Effects of thermal treatments on the conductance of tin oxide - Castro, Miriam Susana (2000)
Temperature dependence of electrical conductivity during heating and cooling under different atmospheres and resistivity transients at step isothermal changes in oxygen pressure of SnO2 sintered pellets are investigated. It is found that different thermal treatments in sample preparation give rise to diverse conductivity behaviors as a function of temperature and transient responses. These results indicate that grain sizes and widths of the depletion layers are responsible for the observed results. Also, oxygen diffusion into the tin oxide grain plays a significant role accounting for the observed conductance changes.